Women service users' experiences of inpatient mental health services and staff experiences of providing care to women within inpatient mental health services: A systematic review of qualitative evidence. (June 2021) - Scholes, A.; Price, O.; Berry, K.
Abstract: Background: With austerity measures and cuts to community mental health services, more women are accessing UK inpatient mental health services. Inpatient services have been found to lead to further retraumatisation for women, exacerbating mental health conditions. However, recent reviews of service user experiences of inpatient services have neglected the unique perspectives of women and have omitted important dynamics in attitudes and experience between staff and women service users. Objectives: The aim of this systematic review was to synthesise women service users' experiences of inpatient mental health services and staff experiences of providing care to women within inpatient mental health services, to appraise the methodological quality of research in this area and provide recommendations for clinical practice and future research. Review methods: A systematic search of the literature was undertaken in the databases: AMED, CINAHL plus, Embase and PsychINFO. The Critical Appraisal Skills Programme checklist for qualitative research was used to evaluate data quality. Thematic synthesis was conducted on papers meeting the inclusion criteria. Results: Eighteen studies were identified and encapsulated the views of 168 staff and 187 service users, with one paper including both staff and service user samples. Three themes derived from the data: Safe haven, Broken system and Therapeutic milieu. Safe haven related to aspects of care such as relational security which made women feel safer in hospital. Broken system pertained to experiences of being fearful of inpatient environments, inadequate acknowledgement of abuse histories, women feeling coerced into compliance with medication and systemic pressures of services being under-resourced. The therapeutic milieu of inpatient services was an important mediator of women experiencing the environment as a 'safe haven' or 'broken system'. Staff and women service users reflected on: the impact on social roles, interaction of peers, physical environment and the importance of meaningful activity, which were deemed to be important contributors to the therapeutic milieu. Conclusions: The review made recommendations to improve future research by encouraging studies to include more detail on reflexivity (including the relationship between researcher and participant) and provide more information on the methodological approach to data analysis. Clinical recommendations include: ensuring staff access clinical supervision, for staff to receive training in exploring and supporting women disclosing experiences of abuse, for staff to facilitate choice within inpatient settings and support women in maintaining relationships, particularly parenting roles. Registration: PROSPERO database (CRD42020156222).